Community Structure of Fish in the Estuary of the Rawa Mekar Jaya Village, Sungai Apit District, Siak Regency - Capah, Roida Mawati; Sumiarsih, Eni; Fajri, Nur El (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRAKThe fisheries potency in the estuary ofRawaMekar Jaya Village is high. A research aims to determine the fishcommunity structure in that estuary was conducted in April-July 2019. Fish samples were taken in 3 stations,in the mangrove area(ST-1), reforestation mangrove area (ST-2) and around the residential area (ST-3). The fishes were captured using fishing rod, net traps (mesh size 1-2 inches) and scoop net (mesh size 0.5 cm). Fish was sampled everyday for 10 days period.  Results shown that the caught fishconsisted of 13 species that are belonged to 12 families. Diversity Index (H ') 2.01–2.31, uniformity index (E) 0.87-0.96 and dominance index (D) 0.10–0.16. The water quality in the estuary were as follows; temperature of 28-300C, the current speed 0.011-0.041 m/sec, brightness of 43-45 cm, salinity of 1,5-15 ‰, dissolved oxygen   3.25-4.16 mg/L and pH of 5-6. Data obtained indicates that community structure of fish can be categorized as medium (stable). Keywords; Coastal, Mangrove, Diversity index.Uniformity index, Dominance index